The Impact Of Public Investment On The Economic Growth In The Libyan Economy - Balq بشير (Journal of Pure & Applied Sciences, 2021)
This paper examines the extent to which there is a stable long-term relationship between public investment and some economic variables, foremost of which is economic growth, whether at the macro or sectoral level in the Libyan economy during the period 1962 – 2010, the period in which data on the relevant variables are available. Using Johansen's methods and the newly developed bound test for cointegration, the results showed the existence of equilibrium relationship between public investment and growth in only some sectors, especially the non-oil and goods sectors. These findings raise doubts about the feasibility of government investment in stimulating economic growth and diversifying the economy.